Practice Question on "Digital Signal Processing"
Topic: Computing a z-transform
Contents
Question
Compute the z-transform (including the ROC) of the following DT signal:
$ x[n]=3^n u[-n+3] \ $
Then use your answer to obtain the Fourier transform of the signal. (Write enough intermediate steps to fully justify your answer.)
You will receive feedback from your instructor and TA directly on this page. Other students are welcome to comment/discuss/point out mistakes/ask questions too!
Answer 1
x[n] = 3nu[-n + 3]
$ X(z) = \sum_{n=-\infty}^{+\infty} x[n] z^{-n} $
$ X(z) = \sum_{n=-\infty}^{+\infty} 3^n u[-n+3] z^{-n} $
Let k = -n+3, n = -k+3
$ X(z) = \sum_{k=0}^{+\infty} (\frac{3}{z})^{-k+3} $
$ X(z) = (\frac{3}{z})^{3} \sum_{k=0}^{+\infty} (\frac{z}{3})^{k} $
$ X(z) = (\frac{27}{z^3}) \sum_{k=0}^{+\infty} (\frac{z}{3})^{k} $
By geometric series formula,
$ X(z) = (\frac{27}{z^3}) (\frac{1}{1-(\frac{z}{3})}) $ ,for |z| < 3
X(z) = diverges, else
So,
$ X(z) = (\frac{3}{3-z}) $ with ROC, |z| < 3
- Grader's comment: Obtain the Fourier transform of the signal
Answer 2
$ X(z) = \sum_{n=-\infty}^{+\infty} x[n] z^{-n} = \sum_{n=-\infty}^{+\infty} 3^n u[-n+3] z^{-n} $
Let k=-n+3, n=3-k, then
$ X(z) = \sum_{k=-\infty}^{+\infty} (3)^{n-k}u[k](z)^{-3+k} $
$ X(z) = (\frac{3}{z})^{3}\sum_{k=0}^{+\infty} (\frac{z}{3})^{k} $
$ X(z) = \left\{ \begin{array}{l l} (\frac{3}{z})^3 \frac{1}{1-\frac{z}{3}} &, if \quad |z| < 3\\ \text{diverges} &, \quad \text{otherwise} \end{array} \right. $
$ \mathcal{F}(x[n]r^{-n}) = X(3e^{jw}) = \mathcal{X}(w) = \frac{\frac{3}{3e^{jw}}}{1-e^{jw}} $
- Grader's comment: The Fourier Transform calculated is wrong
Answer 3
Kyungjun Kim
$ X(z) = \sum_{n=-\infty}^{+\infty} 3^n u[-n+3] z^{-n} $
Let l=-n+3, n=3-l, then
$ X(z) = \sum_{l=-\infty}^{+\infty} (3)^{n-l}u[k]z^{-3+l} $
$ X(z) = (\frac{3}{z})^{3}\sum_{l=0}^{+\infty} (\frac{z}{3})^{l} $
$ X(z) = (\frac{3}{z})^3 \frac{1}{1-\frac{z}{3}} $ if |z| < 3
- Grader's comment: Obtain the Fourier transform of the signal
Answer 4
$ X[Z] = \sum_{n=-\infty}^{+\infty} 3^{n}u[n+3] Z^{-n} $
$ X[Z] = \sum_{n=-3}^{+\infty} 3^{n}Z^{-n} $
$ X[Z] = \sum_{n=-3}^{+\infty} (\frac{3}{z})^{n} $
$ X[Z] = \sum_{n=-3}^{n=-1} (\frac{3}{z})^{n} + \sum_{n=0}^{+\infty} (\frac{3}{z})^{n} $
$ for \sum_{n=-3}^{n=-1} (\frac{3}{z})^{n}, no effect, because this converges everywhere on plane. $
$ for \sum_{n=0}^{+\infty} (\frac{3}{z})^{n}) = \frac{1}{1-\frac{3}{z}}, if |\frac{3}{z}|<1, |z|>3 $
or diverges else.
for the DTFT for this signal,
$ for \sum_{n=0}^{+\infty} (\frac{3}{z})^{n} = \frac{1}{1-\frac{3}{z}}, |z|>3, so it is impossible to have e^{j\omega}, because ROC is bigger at 3 $
$ for \sum_{n=-3}^{n=-1} (\frac{3}{z})^{n}, the DTFT is follow: $
$ \sum_{n=-3}^{n=-1} (\frac{3}{e^{j\omega}})^{n} $
for all, this signal can't have DTFT.
- Grader's comment: You copied the question wrongly
Answer 5
x[n] = 3nu[-n + 3]
$ X(z) = \sum_{n=-\infty}^{+\infty} x[n] z^{-n} $
$ X(z) = \sum_{n=-\infty}^{+\infty} 3^n u[-n+3] z^{-n} $
$ X(z) = \sum_{-\infty}^{3} 3^n z^{-n} $
Let k = -n,
$ X(z) = \sum_{k=-3}^{+\infty} 3^{-k} z^k $
$ X(z) = \sum_{k=-3}^{+\infty} (\frac{z}{3})^{k} $
For |z| < 3, we have, by geometric series, that:
$ X(z) = (\frac{27 z^{-3}}{1+(\frac{z}{3})}) $
By simplification,
$ X(z) = (\frac{-81 z^{-4}}{1-3 z^{-1}}) $, ROC |z| < 3.
Since the ROC contains the unit circle, there exists a Fourier transform representation for the signal. Therefore, to find the signal`s Fourier representation, we just need to replace z be $ e^{j w} $
So,
$ X(\omega) = -(\frac{81 e^{-j 4 w}}{1-3 e^{-j w}}) $
- Grader's comment: Correct Answer
Answer 6
$ x[n] = 3^n u[-n+3] $
$ X(z) = \sum_{n = -\infty}^{\infty} x[n] z^{-n} $
$ = \sum_{n=-\infty}^{\infty} 3^n u[-n+3] z^{-n} $
let k = -n+3 => n = -k+3
$ X(z) = \sum_{k=0}^{\infty} 3^{-k+3} z^{k-3} $
$ = \frac{3^3}{z^3} \sum_{k=0}^{\infty} {\frac{z}{3}}^k $
$ = \frac{3^3}{z^3} \frac{1}{1-\frac{z}{3}}, \left |\frac{z}{3} \right | < 1 $
$ X(z) = \frac{3^3}{z^3} \frac{1}{1-\frac{z}{3}}, \left | z \right | < 3 $
diverges , else
$ F{{x[n]r^{-n}}} = X(3e^{jw}) = X(\omega) = \frac{e^{-j \omega 3}}{1-e^{jw}} $
- Grader's comment: Replace Z by e^jw
answer 7
Xiang Zhang
In order to get Z-transform, we can first apply the basic transformation equation.
$ X_(z) = \sum_{n = -\infty}^{ \infty} x[n] z^{- n} $
Substitute in x[n], we can get that,
$ X_(z) = \sum_{n = -\infty}^{ \infty} 3^n u[-n+3] z^{- n} $
let's use variable substitution by k = -n+3 hence n = 3-k. It can make our life beautiful and easier!
$ X_(z) = \sum_{n = +\infty}^{- \infty} 3^{3-k} u[k] z^{k - 3} $
Now we can use u[k] to change the lower boundary to
$ X_(z) = \sum_{n = 0 }^{ \infty} 3^{3-k} z^{k-3} $
We can take out some terms from Z.
$ X_(z) = \frac{27}{ z^3} \sum_{n = 0 }^{ \infty} {(\frac{z}{3})}^{k} $
Now we can apply geometric series formula into the transform by letting q = z/3
$ \frac{1}{1-q} = \sum_{ n = 0 }^{+ \infty} q^k for |q| < 1 $
$ X_(z) = \frac{27}{ z^3} (\frac{1}{1-\frac{z}{3}}) for |z| < 3 $
Hence, the final x(z) is
$ X(z) = \left\{ \begin{array}{l l} \frac{27}{ z^3} (\frac{1}{1-\frac{z}{3}}) & \quad when \quad |z| < 3\\ diverges & \quad \text{else} \end{array} \right. $
- Grader's comment: Obtain the Fourier transform of the signal